Performance evaluation for Ag and Au nanoparticle containing K2O‐MgO‐B2O3‐Al2O3‐SiO2‐F glass sealants for SOFC application. Issue 2 (13th February 2023) - Garai, Mrinmoy; Roy, Shibayan
Abstract: The present work illustrates the effect of Ag and Au nanoparticle addition on the density, microstructure, phase formation and thermal performance of K2 O‐MgO‐B2 O3 ‐Al2 O3 ‐SiO2 ‐F glass‐ceramics considered as a potential sealant material for solid oxide fuel cell (SOFC) applications. Addition of 0.2 wt.% Ag and Au nanoparticles caused a steep increase in the density of the base glasses in comparison to the glass containing an equivalent amount (0.2 wt%) of Cu nanoparticle. The glass‐ceramics were prepared from the base glasses by controlled heat treatment at 900°C, a temperature relevant for SOFC operation. They were multicrystalline having fluorophlogopite (KMg3 AlSi3 O10 F2 ) as the predominant crystal phase and norbergite (Mg2 SiO4 .MgF2 ) and enstatite (MgSiO3 ) as additional phases. Fluorophlogopite crystals form in both plate‐like and rod‐like morphologies within the glass matrix in the microstructure of the glass‐ceramics. The size of the plate‐shaped fluorophlogopite crystals increases for Ag nanoparticles containing glass‐ceramics in comparison to either Cu or Au nanoparticles containing glass‐ceramics. The density of the Ag and Au nanoparticle glass‐ceramics are also considerably higher due to the formation of a compact interlocked crystalline microstructures. The Au nanoparticle containing glass‐ceramics is characterized by a large thermal expansion (coefficient of thermal expansion, CTE= 11.29 × 10 −6 /K in 50–800°C range) which is comparable to other SOFC components. This glass/glass‐ceramics sealant also possess maximum volume shrinkage in the range of 30–900°C as well as nearly constant CTE without any considerable decrease up to 10 cycles of SOFC operations making it suitable for SOFC sealant applications.